J.L. Petit's triangle lumbar hernia - Campos Pierri, Néstor; Mascari, José Luis; Alvez, Zully (Cirugía del Uruguay, 1989)
Authors present the first national case of lumbar hernia of the Petit variety. They make a revision on the subject of lumbar hernia, specially on this type, and propose that the use of prosthesic material for its repair could be of election.